2021
DOI: 10.1161/jaha.120.019037
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Daytime Napping and Incident Heart Failure in 1140 Community‐Dwelling Older Adults: A Prospective, Observational Cohort Study

Abstract: Background Disrupted nighttime sleep has been associated with heart failure (HF). However, the relationship between daytime napping, an important aspect of sleep behavior commonly seen in older adults, and HF remains unclear. We sought to investigate the association of objectively assessed daytime napping and risk of incident HF during follow‐up. Methods and Results We studied 1140 older adults (age, 80.7±7.4 [SD] years; female sex, 867 [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In the Rush Memory and Aging Project, daytime napping in older adults (81.4±7.5 years of age) was associated with higher risk of HF (per 1-SD increase in square root–transformed nap duration: HR, 1.38 [95% CI, 1.12–1.69]; frequency >1.7 times per day: HR, 2.20 [95% CI, 1.41–3.46]). 41…”
Section: Sleepmentioning
confidence: 99%
“…In the Rush Memory and Aging Project, daytime napping in older adults (81.4±7.5 years of age) was associated with higher risk of HF (per 1-SD increase in square root–transformed nap duration: HR, 1.38 [95% CI, 1.12–1.69]; frequency >1.7 times per day: HR, 2.20 [95% CI, 1.41–3.46]). 41…”
Section: Sleepmentioning
confidence: 99%
“…So far, there are few studies on daytime nap patterns and multimorbidity, but a recent study found that individuals with the high-concave daytime napping duration pattern had a higher risk of hypertension, compared with individuals with a low-stable napping duration pattern [20]. Past studies have found the association of baseline daytime napping duration with metabolic syndrome [31], stroke [32], heart failure [33]. In contrast, a meta-analysis of cohort studies only found an association between daytime napping duration and cardiovascular in women crowds [34].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there could be unmeasured comorbidities that affect both daytime sleep and cognition, for example, sleep apnea 44 . The MAP has started collecting sleep apnea risk scores (Berlin Questionnaire) since 2013, and only few MAP participants had this score available at the time of analysis (i.e., <300 participants) 45 . This can be further examined later when new data become available.…”
Section: Discussionmentioning
confidence: 99%